A xenograft study of human adipose stromal cell‐based vocal fold mucosal replacement in rabbits. Issue 5 (26th September 2022) - Tran, Eric K.; Alhiyari, Yazeed; Juarez, Kevin; Gowda, Bhavani Shankara; Schrader, Feng; Sajed, Dipti P.; Long, Jennifer L.
Abstract: Objectives: Vocal fold (VF) scarring, manifested by increased collagen, decreased glycosaminoglycans (GAGs), and disrupted elastic fibers, remains a negative consequence of VF injury or resection. The objective of this study is to compare four reconstructive options after Vf mucosal resection in rabbits. A Cell‐Based Outer Vocal fold Replacement (COVR) using human adipose‐derived mesenchymal stromal cells (hASCs) in fibrin scaffold is directly compared with a decellularized scaffold implant, hASC injection, and resection alone without reconstruction. The primary hypothesis is that the cells‐in‐scaffold construct better reconstitutes the VF structure than either cells or scaffold alone, or than healing by secondary intention. Methods: A total of49 rabbits received bilateral VF cordectomy, followed by either COVR implant, decellularized scaffold implant, hASC injection, or no reconstruction (injured control group). Larynges were harvested after 6 weeks. Results: Histology demonstrated greater lamina propria thickness, less collagen deposition, and more GAGs in COVR animals versus all other treatment groups. Evidence of persistent human cells was found in about half of the cell‐treated animals. RNA levels of fibrosis pathway and macrophage phenotype markers were statistically unchanged among treatment groups at 6 weeks. Conclusion: These data support the efficacy of COVR implantation in restoring VF microstructure in rabbits. The intact COVR was required; isolated components of decellularized scaffold or injected hASC still produced histologic scarring. We propose that the unique bilayered cell structure within fibrin enables controlled matrix remodeling to minimize wound contraction and fibrosis, and to promote GAG deposition. Level of Evidence: Basic science study